March at the Arch (2001)
Peace Arch Park marCh at THe aRch/ Peace Arch Park commemorates the lasting peace between Canada and the United States. Located at the Blaine border crossing, it is accessible via I-5 North or 99 South. Follow the signs to Peace Arch Park - parking available./ WHAT WE GET Transnational corporations want a seamless "free trade zone" from Tierra-del Fuego to the Arctic Ocean to force the lowest possible wages with no environmental or social responsibility - profits before people./ WHAT'S AT STAKE: - quality public education and equitable health care - democratic community decision making - job security, workers' rights: safe and healthy workplaces - effective environmental protection - control over our future/ say 'NO' to Free Trade Agreement of the Americas! say 'YES' to Fair Trade throughout the Americas!/ AGENDA 10 AM to noon Music and Culture for Fair Trade Noon to 2 PM Speakers, music, theatre and poetry 2 to 4 PM Music and Culture for Fair Trade/ APRIL 21 SATURDAY/ The PEACE ARCH COALITION comprises groups from Canada and the U.S. including Canadian Labour Congress, BC Federation of Labour, Mayworks Festival, King County LC, Council of Canadians, BCTF, BCGEU, Food Not Bombs, HEU, Whatcom County Rainbow Coalition, CAW Canada, Trading Strategies, Snohomish County LC, Vancouver & District LC, CFS, MobGlob, Whatcom County LC, Veterans Against Nuclear Arms, Colmena Collective, Students Against the FTAA, Walk For Democracy, Pierce County Central LC, Shuksan Direct Action, ASJE, Unitarian Universalist Church, CUPE-BC, Radical Cheerleaders, ANWA, TUG, Whitman Insurgency, Repeal The Deal, Solidarity Notes, Seattle Peace Chorus, New Westminster & District LC. PPWC, Intl. Longshore Warehouse Union, ILWU L 19, ILWU L 400, ILWU L500, ILWU Puget Sound BC, Inlandboatmens Union/ILWU, North Shore CofC, CPC-ML, UBC Social Justice, Intl. Socialists, Seniors Network BC, CUPW - Vancouver, CEP Canada, CPC, Vancouver Rape Relief, MWBIU, CAW L 1990, Working TV, PSAC, SPEEA L201 - IFPTE, International Federation of Professional Technical Engineers, Women's Intl. League of Peace & Freedom BC, LEAS, Teamsters L174, Intl. Socialist Org, TWU, APWU L28, APWU Greater Seattle, SEIU-CSA Local 925, DCLC, Tacoma Catholic Worker, Mad River Puppets, CESAPI, American Lands Alliance, CAP, UFCW L1518, Vancouver CDWCR, CAW L114, Pacific Maritime Council, CAW L111, Canadian Unitarians For Social Justice, CAW L3000, CAW L2200, CAPRN, Open the Borders!, Check Your Head, Ogoni Solidarity Network, SANSD, Whatcom Green Party, BC Prov. Council of Carpenters, SPEC, NAc, UFAWU-CAW/ MAKING HISTORY Canadians and Americans have a long history of working together for social causes. On May 18, 1952, thousands of Canadians and Americans gathered in Peace Arch Park to listen to singer and political activist Paul Robeson, barred entry to Canada during the McCarthy era./ LOCAL CONTACTS/ FOR INFO or BUSES FROM VANCOUVER phone VDLC (604) 254-0703 FOR INFO FROM SEATTLE, phone ILWU (206) 284-5040 Ext. 27 or check out our website at www.stopftaa.org/peacearch/ WORKING DESIGN 2001/ MARINE PRINTERS/ PHOTOS TOP JEF KEIGHLEY CENTRE COURTESY CHECK YOUR HEAD BOTTOM PACIFIC TRIBUNE